A realistic expectation of electricity production from current design concentrated solar power solar tower with thermal energy storage. Issue 3 (22nd May 2019) - Boretti, Alberto
Abstract: The costs and electricity production of concentrated solar power (CSP) solar tower (ST) with molten salt (MS) thermal energy storage (TES) technology are here analyzed for the latest, recently dismissed, Aurora project. For a 135 MW net nominal capacity, the likely electricity production is less than the planned 495 GWh/year, corresponding to a capacity factor (CF) of 42%. The dispatchability of this electricity production is also less than the expected. The costs of the electricity produced by this technology are larger than the AU$ 78/MWh of the power purchase agreement (PPA). The larger costs are due to the large‐scale generation certificates (LGCs), valued at around AU$80/MWh, the low‐interest loan of 110 m$AU, and the indirect costs of the larger share of intermittent and unreliable electricity. In a state with peak power prices already up to AU$14000/MWh, the peak power costs are indeed expected to rise further, if the PPA does not specify any minimum amount of electricity to be produced. Given the electricity production of the similar plant of Crescent Dunes, one‐third of the planned, despite more than double the cost, it has been impossible to secure the investments needed even at a cost of AU$ 158/MWh.